The Haemophilia Health Journey: Experiences and Unmet Care Needs of Caregivers and Their Young Children - Caroline M. A. Mussert; Eva K. Kempers; Evelien S. van Hoorn; Ekin Kerimoğlu; Marijke Melles; Mathieu A. Gielen; Armaĝan Albayrak; Kees T. B. Ahaus; Simone H. Reitsma; Samantha C. Gouw; Marjon H. Cnossen (Haemophilia, 2026)
ABSTRACT Introduction Understanding patients’ and caregivers’ experiences, values and needs is essential to implement patient‐centred care. However, specific insights into how young children with haemophilia and their caregivers experience the entire care trajectory, from diagnosis onwards, remain limited. Aim Gain an in‐depth understanding of the experiences and needs of caregivers of young children (0–10 years) with haemophilia regarding haemophilia care and daily life, as well as children's own perspectives. Methods A qualitative interview study was conducted applying purposive sampling to select a varied sample regarding haemophilia type, disease severity, treatment modality and the child's age. Interviews were conducted until saturation was reached, followed by a comprehensive thematic content analysis including multiple phases of coding. Results In total, 27 interviews were conducted (38 caregivers, 15 children). Twenty‐five subthemes emerged related to four care pathway phases, and daily life. Caregivers emphasized that haemophilia knowledge among healthcare providers outside treatment centres, information provision, access to peer support and remote healthcare can be improved. Haemophilia had psychological, social and occupational impacts on caregivers. Impact on daily life was variable and primarily influenced by bleeding phenotype, and family history. Lastly, caregivers highlighted the importance of child‐centred care, maintaining haemophilia awareness and the benefits of prophylaxis and self‐administration. Conclusion To further enhance patient‐centred care, caregivers expressed the need for a tailored and centrally available information resource, expansion of remote healthcare services and increased haemophilia knowledge. Furthermore, healthcare providers should be more aware of the multifaceted impact of haemophilia on caregivers and the factors influencing haemophilia impact on daily life.